Prolonged grief and posttraumatic stress disorder following the loss of a significant other: An investigation of cognitive and behavioural differences. - Kirsten V Smith; Anke Ehlers (PLoS ONE)
Background Cognitive behavioural correlates to bereavement-related mental health problems such a Prolonged Grief Disorder (PGD) and Posttraumatic Stress Disorder (PTSD) are of theoretical and clinical importance. Methods Individuals bereaved at least six months (N = 647) completed measures of loss-related cognitions and behaviours (i.e., loss-related memory characteristics, negative appraisals, coping strategies, grief resilience, and perceived social disconnection) and measures of PGD and PTSD symptoms. Individuals were assigned to one of four groups depending on probable clinical diagnoses (No-PGD/PTSD, PTSD, PGD, PGD+PTSD). Results Results indicated that higher loss-related memory characteristics and lower grief resilience increased the likelihood of a clinical problem. The PGD and PGD+PTSD groups reported significantly higher loss-related memory characteristics and appraisals compared to the PTSD group. Social disconnection increased the likelihood of comorbid PGD+PTSD in comparison to any other group. Conclusions Results indicate cognitive differences between loss-related cognitions, memory characteristics and coping strategies between PGD and PTSD, and points to distinct cognitive correlates to psychopathology following loss.